2010
DOI: 10.1039/c0jm01852j
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive and mechanically strong biomimetic chitosan/reduced graphene oxide composite films

Abstract: Composite films of chitosan and reduced graphene oxide (RGO) sheets with nacre-like layered structure have been prepared by vacuum filtration of the stable aqueous mixture of both components. The film containing 6 wt% RGO is electrically conductive with a conductivity of 1.2 S m À1 . Furthermore, it is mechanically strong and ductile; its Young's modulus, tensile strength and elongation at break were measured to be 6.3 AE 0.2 GPa, 206 AE 6 MPa and 6.5 AE 0.6%, respectively. These values partly exceed those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
166
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(176 citation statements)
references
References 52 publications
7
166
3
Order By: Relevance
“…Composite fi lms of CS and rGO sheets with nacre-like layered structure were fabricated by vacuum fi ltration. [ 68 ] The results indicated that the uniform dispersion of rGO nanofi llers in the polymer matrices resulted in the high electrical properties of CS/rGO composite fi lms. In comparison to conventional fi lled polymers, graphene/polymer composites containing extremely lower graphene show superior electrical conductivity.…”
Section: Utilization Of the Electrical Properties Of Graphenementioning
confidence: 98%
“…Composite fi lms of CS and rGO sheets with nacre-like layered structure were fabricated by vacuum fi ltration. [ 68 ] The results indicated that the uniform dispersion of rGO nanofi llers in the polymer matrices resulted in the high electrical properties of CS/rGO composite fi lms. In comparison to conventional fi lled polymers, graphene/polymer composites containing extremely lower graphene show superior electrical conductivity.…”
Section: Utilization Of the Electrical Properties Of Graphenementioning
confidence: 98%
“…The amazing properties (self-polymerization, reduction, and adhesion) of dopamine make it possible to use it simultaneously as a reducing agent for GO and as an adhesive similar to the mortar in nacre to crosslink lamellar graphene in situ. Although nacre-like graphene composites have been fabricated using different approaches, [48][49][50] in our case, the resultant paper-like GC demonstrates stable superhydrophobicity, self-cleaning, and remarkable mechanical properties underwater, exhibiting multifunctional integration.…”
Section: Introductionmentioning
confidence: 97%
“…19,20 More specifically, a number of authors have shown that the addition of GO can improve the mechanical properties of chitosan films significantly 21,22 and there are some reports on the effects of graphene oxide on the biocompatibility of graphene-chitosan composite films. 10,23 However, very little work has been done to study the effect of the addition of well dispersed, electrically conductive graphene nanosheets on the chitosan matrix.…”
Section: Introductionmentioning
confidence: 99%